SRFACS: A secure and robust framework for anonymous communication systems. - Daxin Zhu; Jiazhi Tu; Danlin Cai; Tianyu Jiang; Jianbing Xiahou; Yusi Chen; Chao Liu (PLoS ONE)
Anonymous communication is crucial for preserving user privacy in various applications, such as anonymous browsing, secure online payments, and electronic voting. However, current systems face significant challenges related to robustness, fault tolerance, and efficient communication management. This paper introduces SRFACS (Secure and Robust Framework for Anonymous Communication Systems), designed to address these issues by integrating advanced cryptographic techniques with a structured communication framework. Traditional anonymous communication systems usually lack sufficient fault tolerance, making them vulnerable to node failures, especially in asynchronous environments. In order to overcome these limitations and ensure that the system can keep running in the event of node failure (especially in an asynchronous environment), SRFACS integrates an improved asynchronous Byzantine Fault Tolerant (ABFT) protocol. We use this protocol to expand the traditional single communication node into a structured node group, and handle up to (n - 1)/3 faulty nodes in these groups, so as to enhance fault tolerance and maintain continuous operation. To efficiently manage inter-group communication, SRFACS utilizes leader nodes to coordinate and streamline the communication processes. To mitigate the risks associated with leader failures, we have implemented an efficient leader change protocol that promptly replaces defective leaders, ensuring uninterrupted system performance. Additionally, to prevent erroneous leader actions from compromising the system, we have introduced an advanced multi-signature scheme. This approach secures communication by requiring multiple signatures for verification processes. Furthermore, we have implemented a reputation incentive mechanism to encourage nodes to maintain optimal performance and avoid malicious behavior. This mechanism evaluates nodes according to their past activities and reliability to achieve dynamic updates of SRFACS node groups. We have conducted rigorous security analyses and component performance evaluations of SRFACS, further confirming its potential as a promising secure communication solution.